1995
DOI: 10.1093/infdis/171.1.240
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification Of A Point Mutation Of The Mycobacterium tuberculosis Catalase-Peroxidase (katG) Gene Associated With Isoniazid Resistance

Abstract: The complete catalase-peroxidase (katG) gene DNA sequence was determined for 15 strains of Mycobacterium tuberculosis with a wide range of susceptibility to isoniazid. Five of 9 strains with isoniazid MICs > or = 1.0 microgram/mL had one or more missense mutations and all 5 strains had a common G-->T transversion in codon 463, causing the replacement of arginine with leucine and the loss of an NciI or MspI restriction site. None of 6 strains with an isoniazid MIC < 1.0 microgram/mL had mutations affecting codo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 10 publications
3
68
0
1
Order By: Relevance
“…However, in previous studies, the mutation at codon 463 was found in 3 to 61% of INH-susceptible M. tuberculosis isolates (5,6,13,17,18,23). Also, it was found that the activity of catalase, a katG-encoded enzyme, did not differ among isolates having either Arg or Leu at codon 463 (21,22).…”
Section: Tuberculosis Isolates and Assessment Of Inh Resistancementioning
confidence: 87%
See 1 more Smart Citation
“…However, in previous studies, the mutation at codon 463 was found in 3 to 61% of INH-susceptible M. tuberculosis isolates (5,6,13,17,18,23). Also, it was found that the activity of catalase, a katG-encoded enzyme, did not differ among isolates having either Arg or Leu at codon 463 (21,22).…”
Section: Tuberculosis Isolates and Assessment Of Inh Resistancementioning
confidence: 87%
“…The genetic mechanism of INH resistance remains unknown for 10 to 15% of the INH-resistant isolates. The mutations in katG occur in 50 to 60% of the INH-resistant isolates at codon 315 and in 25 to 45% of these isolates at codon 463 (5,16,17).…”
Section: Tuberculosis Isolates and Assessment Of Inh Resistancementioning
confidence: 99%
“…By contrast, INHresistant strains exhibit mutations in several genes, such as katG, inhA, oxyR, and ahpC (22,27,30). The mutation of codon 315 (Ser) in the catalase-peroxidase (katG) gene is the most frequent site (30 to 65% of resistant strains) (4,11). Furthermore, EMB-resistant strains have a point mutation at codon 306 (Met) in embB (3,28), and the frequency is about 70% (3).…”
mentioning
confidence: 99%
“…The presence of R463 or L463 at codon 463 and the presence of S315T substitution in the katG gene was determined by amplification of the corresponding katG gene DNA region by PCR followed by restriction endonuclease digestion of the PCR amplified fragments to generate restriction fragment length polymorphism as described previously (1,5).…”
mentioning
confidence: 99%